Revisão sistemática sobre dança para autistas - Diniz, Júlia Souza (2024)
Introduction: Dancing is a form of expression and communication performed through rhythmic and synchronized movements. Dance practice is associated with the activation of different areas of the brain, mainly areas related to emotions, cognition, movement, communication and socialization. Therefore, this review aims to identify studies that report the benefits of dancing for autistic people with all levels of support. Method: The research question was what are the impacts of dance practiced by autistic persons? The study selection process consisted of 3 phases. First, the studies were identified through search strategies defined in the databases: Psycinfo, PubMed, Science Direct, Web of Science and Google Scholar. In the second phase, articles were selected by reading the abstracts and in the third phase by reading the full text. Results: We selected 27 studies for this review. After analyzing the studies, it was possible to observe that dance can influence (1) sensory and emotional experiences, (2) social relationships, (3) cognition, (4) body awareness and motor skills, (5) characteristics of autism. The included studies reported that dance can promote positive sensory experiences, which contributes to overcoming the socialization difficulties present in autism. Dance favors the understanding of body language and promotes verbal and non-verbal communication. In addition, it contributes with cognitive functions, such as attention, memory, planning and imagination, and motor skills, promoting balance. Conclusion: The studies reported different outcomes and forms of assessment that made difficult to compare the results obtained by the selected studies. However, it was possible to perceive that dance contributes to the well-being and quality of life of autistic people.